2015
DOI: 10.1089/mdr.2014.0153
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Community-Associated Methicillin-ResistantStaphylococcus aureusIsolated from Skin and Pus Samples of Outpatients in Japan

Abstract: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is now endemic in the United States. In Japan, CA-MRSA infections and CA-MRSA surveillance have been scarcely reported. In this study, we conducted a nationwide survey of CA-MRSA in Japan. We collected MRSA strains isolated from outpatients with skin and soft-tissue infection (SSTI) at 107 medical facilities from 24 prefectures in 2010 and 2012. Among 10,385 clinical samples from SSTI patients, 3,581 S. aureus isolates (35%) were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…From our genetic analysis, the percentage of SCC mec type II was higher than that of SCC mec type IV. On the other hand, in the previous nationwide surveillance of CA‐MRSA isolated from skin and pus samples of outpatients in Japan, the most frequent SCC mec type was IV and the second was II . However, there were some differences in study design between the two nationwide surveillances.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…From our genetic analysis, the percentage of SCC mec type II was higher than that of SCC mec type IV. On the other hand, in the previous nationwide surveillance of CA‐MRSA isolated from skin and pus samples of outpatients in Japan, the most frequent SCC mec type was IV and the second was II . However, there were some differences in study design between the two nationwide surveillances.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, the susceptibility rate of fluoroquinolone was lower in HA‐ than in CA‐MRSA, but there was no significant difference. Previous studies reported that antibiotic susceptibility was different between HA‐ and CA‐MRSA …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations